Schumpeterian Banks: Credit Reallocation and Capital Requirements - Michael Kogler; Christian Keuschnigg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Capital reallocation from unprofitable to profitable firms is a key source of productivity gain in an innovative economy. We present a model of credit reallocation and focus on the role of banks: Weakly capitalized banks hesitate to write off non-performing loans to avoid a violation of regulatory requirements. This results in insufficient credit reallocation across sectors and a distorted capital allocation. Reducing the cost of equity and tightening capital requirements can mitigate distortions.
Keywords: D92; G21; G28; G33; 330